Substantiating Ways of Load Application When Modeling Interaction of a Multiincisal Mining Machine Actuator With Rocks; IOP Conference Series: Materials Science and Engineering; Vol. 127 : Urgent Problems of Modern Mechanical Engineering - Aksenov V. V. Vladimir Valerievich; Beglyakov V. Yu. Vyacheslav Yurievich; Kazantsev A. A. Anton Aleksandrovich; Saprykin A. S. (2016, 2016)
Title screen